Representation of Visual and Gender Meanings in Indonesian High School Textbooks - Kholifah; Inayatillah, Fafi (Journal of Indonesian Literacy and Indigenous Culture, 2025)
Textbooks are learning media used by schools to convey knowledge that becomes a guide for teachers in the teaching and learning process. Visual text contained in Indonesian language teaching materials for high school students should be able to support understanding in the material to be taught, not make it more confused because of their limited understanding in interpreting the visual text. Visual text can create meaning in language learning. This study aims to analyze visual texts and describe gender representation in Indonesian textbooks for senior high school students. This research analyzes the meaning of representation of visual text and the position of visual text in the realm of gender. The method used is descriptive qualitative. The data is in the form of textual images that show gender identity. the data is collected from high school textbooks grade XI. Data collection was done by reading textbooks, marking, classifying, and counting gender identity markers. The data were analyzed by reducing, presenting, calculating the percentage of representation of visual text, representation of gender identity, interpreting and explaining the gender representation. The results showed that the representation of the meaning of visual text supports the theory of visual representation proposed by Kress and Van Leeuwen. Images in the revised edition of Indonesian textbooks for Class X SMA play an important role in supporting students' understanding and engagement in learning, as well as strengthening understanding of social and cultural contexts. In addition, this textbook shows results that reflect unequal gender representation patterns. Male gender findings tend to be depicted more frequently and in a more dominating role.